XAP5 CIRCADIAN TIMEKEEPER Positively Regulates RESISTANCE TO POWDERY MILDEW8.1–Mediated Immunity in Arabidopsis - Xu, Yong-Ju; Lei, Yang; Li, Ran; Zhang, Ling-Li; Zhao, Zhi-Xue; Zhao, Jing-Hao; Fan, Jing; Li, Yan; Yang, Hui; Shang, Jing; Xiao, Shunyuan; Wang, Wen-Ming (Frontiers in Plant Science, 2017)
Ectopic expression of the Arabidopsis RESISTANCE TO POWDERY MILDEW8.1 (RPW8.1) boosts pattern-triggered immunity leading to enhanced resistance to different pathogens in Arabidopsis and rice. However, the underlying regulatory mechanism remains largely elusive. Here, we report that XAP5 CIRCADIAN TIMEKEEPER (XCT, At2g21150) positively regulates RPW8.1-mediated cell death and disease resistance. Forward genetic screen identified the b3-17 mutant that exhibited less cell death and susceptibility to powdery mildew and bacterial pathogens. Map-based cloning identified a G-to-A point mutation at the 3' splice site of the 8th intron, which resulted in splicing shift to 8-bp down-stream of the original splice site of XCT in b3-17, and introduced into a stop codon after two codons leading to a truncated XCT. XCT has previously been identified as a circadian clock gene required for small RNA biogenesis and acting down-stream of ETHYLENE-INSENSITIVE3 (EIN3) in the ethylene-signaling pathway. Here we further showed that mutation or down-regulation of XCT by artificial microRNA reduced RPW8.1-mediated immunity in R1Y4, a transgenic line expressing RPW8.1-YFP from the RPW8.1 native promoter. On the contrary, overexpression of XCT in R1Y4 background enhanced RPW8.1-mediated cell death, H2O2 production and resistance against powdery mildew. Consistently, the expression of RPW8.1 was down- and up-regulated in xct mutant and XCT overexpression lines, respectively. Taken together, these results indicate that XCT positively regulates RPW8.1-mediated cell death and disease resistance, and provide new insight into the regulatory mechanism of RPW8.1-mediated immunity.